Wind disturbance rejection for an insect-scale flapping-wing robot - Chirarattananon, Pakpong; Ma, Kevin Y.; Cheng, Richard; Wood, Robert J. (2015 IEEE RSJ International Conference on Intelligent Robots and Systems (IROS), 2015)
Despite having achieved unconstrained stable flight, the insect-scale flapping-wing robot is still tethered for power and control. Towards the goal of operating a biologically-inspired robot autonomously outside of laboratory conditions. In this paper, we simulate outdoor disturbances in the laboratory setting and investigate the effects of wind gusts on the flight dynamics of a millimeter-scale flapping wing robot. Simplified models describing the disturbance effects on the robot's dynamics are proposed, together with two disturbance rejection schemes capable of estimating and compensating for the disturbances. The proposed methods are experimentally verified. The results show that they reduced the root mean square position errors by approximately 50% when the robot was subject to 60 cm·s -1 horizontal wind.